2017
DOI: 10.11114/bms.v3i4.2650
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Digital Growth in Modern Business

Abstract: Target research in this paper is the assessment and analysis of content of digital progress and its impact on modern business. Business digitization has been introducing increasingly dynamic changes across the entire global economic sphere, whereas its content increasingly maintains to affect the competitiveness of national economies. At the microeconomic level, digital technologies lead to a change of economic structure and quality of production factors, based on knowledge and innovations. This paper should p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…:8 Issue:2 Year:2020 2388 digitalized economies on the basis of ICT accounted for more than 22% of the global modern business world. Therefore, in the light of these results, it can be concluded that ICT cannot fully integrate and influence the modern business world (Mastilo, 2017).…”
Section: Bmij (2020) 8 (2):2384-2413mentioning
confidence: 98%
See 1 more Smart Citation
“…:8 Issue:2 Year:2020 2388 digitalized economies on the basis of ICT accounted for more than 22% of the global modern business world. Therefore, in the light of these results, it can be concluded that ICT cannot fully integrate and influence the modern business world (Mastilo, 2017).…”
Section: Bmij (2020) 8 (2):2384-2413mentioning
confidence: 98%
“…By means of ICT, enterprises can innovate their products and services, publish information and news related to enterprise in digital media, develop creative and flexible business strategies and take many more actions (Weill, Subramani, & Broadbent, 2002). Furthermore, ICT is the most important tool that can be used to maintain and strengthen the strategic competitive advantage in a constantly changing and developing business world (Mastilo, 2017). Bhatt and Grover (2005) suggested that advanced ICT features give the enterprise the skill to protect against threats and to intervene rapidly in assessing the opportunities that will arise.…”
Section: Information and Communication Technologiesmentioning
confidence: 99%
“…Some authors stated that the increase of the IT production in economic output may increase the overall level of productivity of a country (Albers, 2006). Some research showed that 22% of the global economy is actually digital economy which proves that countries as well as business and individual should invest more in ICT as a development potential area (Mastilo, 2017). Additionally, same paper quotes Oxford study in 2016 which predicts that the development of the digital economy by 2020 would contribute to the economic growth of 25% (Mastilo, 2017).…”
Section: Eu Policies In Order To Develop Tech Sectormentioning
confidence: 99%
“…In one of his papers Mastilo identifies four key impacts of the digital economy on today's global economy: it created a new use-value of products and services, it has a destructive impact which threatens traditional business, it created a new way of communication and it a chance for creation of new jobs (Mastilo, 2017). In the USA it has influenced in creation of 500000 new jobs which could be also a role model and example for economies of the Southeast European countries (Mastilo, 2017). Some authors stated that the increase of the IT production in economic output may increase the overall level of productivity of a country (Albers, 2006).…”
Section: Eu Policies In Order To Develop Tech Sectormentioning
confidence: 99%
See 1 more Smart Citation